Contribuição a análise e projeto de torres autoportantes de linhas de transmissão - Carlos Roberto Gontijo (1994)
This work presents a study of analysis and techniques for self supporting steel transmission towers. The determination of the loadings is describeb, as well as the analysis method used to find member and foundation loads. The formulation of the classical process to determine member loads and to design structural members and connections is described. Next, computer flowcharts for automatic tower design are presented, including geometry and load case generation, analysis using the stiffness method and member and connection design. Finally, the analysis of a tower is performed and the obtained results using the classical and the stiffness methods are compared.